General Hospital Managers' Perception Regarding Crisis Management at Iran and Tehran University of Medical Sciences - Seyed Hesam Seyedin; Ruholah Zaboli; Zeynab Malmoon; Fatemeh Rajabifard (Tehran University of Medical Sciences, 2016)
Background: Today, due to the diversity of organizational structure and culture, the diversity is one of the basic principle in crisis management.Crisis management consists of six components including flexibility, inclusion, trust, risk perception, adaptability and equity.This study aimed at investigating the managerschr('39') perception about components of crisis management in hospitals affiliated to Tehran and Iran University of Medical Sciences. Materials and Methods: This study was a cross-sectional one. A questionnaire was used to collect data using five likert scale. Validity and reliability of questionnaire assessed by content validity and Cronbachchr('39')s alpha coefficient. Sixty six questionnaire were collected. Data analysis was performed by SPSS software using ANOVA and independent t-test. Results: The highest and the lowest level of managerschr('39') perception were inclusion and equity(3.19 ± 0.51) and adaptability(2.73 ± 0.75), respectively. There was a statistical significant difference between crisis management components with gender and job type. The highest level of importance was regarded to inclusion and mutual trust between personnel and managers, and  the lowest level was related to flexibility in hospital crisis management . Conclusion: Employees in diverse positions have different definitions of adaptability in crisis. It is necessary to perform further research and educate hospital manager's duties.